(untitled) (Modern education and development, 2024)
This article delves into the transformative potential of collaborative assessment in enhancing reading and writing instruction. It highlights the benefits of peer review, where students actively engage in evaluating each other’s work, providing constructive feedback, and receiving valuable insights. The article explores how collaborative assessment fosters deeper understanding, encourages critical thinking, promotes self-reflection, and cultivates a supportive learning environment. Practical strategies for implementing collaborative assessment are provided, along with tips for creating effective peer review rubrics and fostering a culture of respectful and constructive feedback. В этой статье рассматривается преобразующий потенциал совместной оценки в улучшении обучения чтению и письму. В ней подчеркиваются преимущества взаимной оценки, когда учащиеся активно участвуют в оценке работы друг друга, предоставляя конструктивную обратную связь и получая ценную информацию. В статье рассматривается, как совместная оценка способствует более глубокому пониманию, поощряет критическое мышление, способствует саморефлексии и создает благоприятную учебную среду. Приводятся практические стратегии внедрения совместной оценки, а также советы по созданию эффективных рубрик взаимной оценки и формированию культуры уважительной и конструктивной обратной связи.